SEMANTIC STUDY OF AL-HARB WORDS IN THE QUR'AN ACCORDING TO THE AZ-ZUHAILI WAHBAH - Ahmad Ridla Syahida (International Journal of Islamic Khazanah, 2019)
This research is a semantic study that aims to uncover the underlying meanings and relational meanings of the word al-qitÄl and al-harb contained in the Koran. Lafadz al-qitÄl and its derivation are repeated 65 times, while the phrase al-harb and their origin are only repeated nine times. With this semantic approach to the word, it is expected to be able to provide a deeper understanding and provide a world view of the Koran. This study also aims to find out how the sources, methods, and interpretations of Wahbah Az-Zuhaili are interpreted in Al-Munir so that they can find out and explore the various characteristics of their understanding of the words al-qital and al-harb in that interpretation. The method used in this research is a descriptive-analysis method to describe and analyze data. The type of data used in this study is qualitative. In contrast, the primary data source used in this study is Al-Munir's interpretation supported by other sources relevant to the object of this study. The results of this study indicate that in terms of the origin of understanding Wahbah Az-Zuhaili tries to combine the interpretation of bil ma'tsur and the interpretation of bil ma'qul (ar-ra'yi), with the style of language and contemporary approaches Wahbah Az-Zuhaili works to present a solutive analysis and under the conditions of the times.